Importance of decision quality in breast cancer care - Sepucha, Karen R.; Belkora, Jeffrey (Psicooncología, 2010)
Background: In breast cancer, treatment decisions are challenging as patients, their families and providers need to sort through an ever expanding array of options for surgery, radiation, reconstruction and systemic therapy. Objective: To describe efficacy and effectiveness of interventions designed to improve decision quality in breast cancer care. Methods: We describe the competencies required of providers and patients to engage in shared decision making, and then present interventions and metrics that have been shown to improve the quality of medical treatment decisions. A case study illustrates how decision support tools have been implemented in a cancer center in the United States. Results: Patients and providers face multiple decisions after a breast cancer diagnosis and too often these decisions are made without patients having adequate information or involvement. Decision aids, prompt sheets and consultation recordings have been shown to improve the quality of decisions by increasing knowledge, reducing decision conflict and improving communication. These tools have been successfully integrated in a variety of cancer centers, but require some resources and infrastructure to make it work. Conclusions: Patients, their families and providers need to work together to select cancer treatments. These interactions are complex and can be improved through the implementation of decision support.
Keywords: Decision making; Decision aids; Breast cancer